2009
DOI: 10.1001/archinternmed.2008.540
|View full text |Cite
|
Sign up to set email alerts
|

Multivitamin Use and Risk of Cancer and Cardiovascular Disease in the Women's Health Initiative Cohorts

Abstract: Context Millions of postmenopausal women use multivitamins, often believing that supplements prevent chronic diseases such as cancer and cardiovascular disease. Objective To examine associations between multivitamin use and risk of cancer, cardiovascular disease and mortality in postmenopausal women. Design, Setting and Participants 161,808 participants from the Women’s Health Initiative Clinical Trials (n=68,132 in three overlapping trials of hormone therapy, dietary modification and calcium-vitamin D) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 54 publications
5
121
1
3
Order By: Relevance
“…[26][27][28][29][30][31] No heterogeneity was detected (I 2 5 4.9%, p 5 0.39). The current analysis includes five out of 13 cohorts from the Pooling Project, 21 while three cohorts of our analysis were not included in the pooled analyses.…”
Section: Multivitamin Supplementsmentioning
confidence: 94%
See 2 more Smart Citations
“…[26][27][28][29][30][31] No heterogeneity was detected (I 2 5 4.9%, p 5 0.39). The current analysis includes five out of 13 cohorts from the Pooling Project, 21 while three cohorts of our analysis were not included in the pooled analyses.…”
Section: Multivitamin Supplementsmentioning
confidence: 94%
“…Finally, most of the studies reported on multivitamin use in general. [26][27][28]30,31 However, the composition of the multivitamins in those studies is unclear as the authors did not further specify whether the supplements contained vitamins only, or also included minerals. The study of Park et al 31 described that their questionnaire included questions about the use of multivitamins (with or without minerals), but in their analyses it was not clear which type of multivitamins, that is, with or without minerals, they had studied.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies could not find significant effectiveness of vitamin E on prevention of cancer, 4,7-25 reduction in cardiovascular diseases, 8,13,25-36 and overall mortality reduction. 5,15,19,25,27,[37][38][39] In a randomized, double-blind, placebo-controlled trial (The Physicians' Health Study II), a total of 14641 male physicians aging more than 50 years were enrolled. They received supplements of vitamin E (400 IU) every other day and were followed for 8 years.…”
Section: Vitamin E (α-Tocopherol)mentioning
confidence: 99%
“…Regular multivitamin pills differ from mega vitamins in the sense that the latter refers to high doses of vitamins as compared to standard multivitamin pills. The Women's Health Initiative study has shown no link between multivitamin supplementation and risk of lung cancer, colorectal cancer, breast cancer, endometrial cancer, ovarian cancer, and cardiovascular and total mortality in postmenopausal women [128]. The Iowa Women's Health Study of 38,772 older women confirmed that many commonly used dietary vitamin and mineral supplements may be associated with increased total mortality risk; the association was strongest with iron, while calcium was associated with diminished risk [129].…”
Section: Misuse and Megadoses Of Vitaminsmentioning
confidence: 99%